ECTOPIC ACTH SYNDROME SECONDARY TO METASTATIC NEUROENDOCRINE CARCINOMA FROM A PRIMARY MEDIASTINAL TUMOUR - LY, Evelyn Khaw; Vergis, Melissa; Devaraja, Vanusha; Ping, Lee Siow; Qingci, Goh (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND We report a case of ectopic ACTH syndrome secondary to metastatic neuroendocrine neoplasm of the anterior mediastinum. CASE A 26-year-old male was diagnosed at age 23 to have ectopic ACTH syndrome secondary to neuroendocrine tumour of mediastinum, size 7 × 6 cm. Gallium-68 DOTATATE PET-CT revealed somatostatin receptor (SSTR) avid disease in the mediastinum only, Krenning 3. He underwent surgical excision and achieved remission postoperatively. Histopathologic examination reported ACTH-producing typical mediastinal carcinoid with nodal involvement, Ki-67 ~10%, mitosis count 1 per 10 high power field, and metastatic typical carcinoid of the excised para-aortic lymph node. Six months later, ACTH was noted to be increasing in trend although he was not Cushingoid clinically. FDG and DOTATATE PET-CT scan revealed metastatic lymphadenopathy to the left supraclavicular fossa and mediastinum with low SSTR affinity (Krenning score 1 and 2). He was referred to the surgical and oncology team for further treatment. However, he opted for a second opinion in an overseas institution and started proton therapy and everolimus there, which was discontinued within weeks due to side effects. He presented again a year later, not overtly Cushingoid, but he then developed more prominent Cushingoid signs and hypokalaemia within months. Biochemical investigation showed persistent disease with increasing ACTH. Ketoconazole was initiated. DOTATATE and FDG PET-CT imaging revealed progressive metastatic lymphadenopathy involving cervical, supraclavicular, mediastinal and coeliac regions. The lesions had concordant FDG and DOTATATE avidity but were more FDG-avid (DOTATATE avidity Krenning 2). Multidisciplinary team discussion concluded a diagnosis of neuroendocrine carcinoma with progressive disease, thus requiring chemotherapy. He was referred to the oncology team but remained undecided about proceeding further. CONCLUSION Neuroendocrine tumours can have heterogeneity in grade within a given lesion, in different sites, and over time. SSTR PET imaging aids in stratifying tumour differentiation thus guiding diagnostic and therapeutic decisions, as illustrated in this case.